2022
DOI: 10.1002/smll.202107910
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Surface Construction for Long‐Term Cycling Stability of Li‐Rich Mn‐Based Layered Oxide Cathode for Li‐Ion Batteries

Abstract: Li‐rich Mn‐based layered oxides (LMLOs) are promising cathode material candidate for the next‐generation Li‐ion batteries (LIBs) of high energy density. However, the fast capacity fading and voltage decay as well as low Coulombic efficiency caused by irreversible oxygen release and phase transition during the electrochemical process hinder their practical application. To solve these problems, in the present study, a multifunctional surface construction involving a coating layer, spinel‐layered heterostructure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…All samples are indexed with a hexagonal α-NaFeO 2 structure belonging to the space group of R -3 m . The weak diffraction peaks located at 20–25° are assigned to the superlattice honeycomb ordering of the monoclinic Li 2 MnO 3 phase . No diffraction peaks belonging to other impurity phases are identified.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…All samples are indexed with a hexagonal α-NaFeO 2 structure belonging to the space group of R -3 m . The weak diffraction peaks located at 20–25° are assigned to the superlattice honeycomb ordering of the monoclinic Li 2 MnO 3 phase . No diffraction peaks belonging to other impurity phases are identified.…”
Section: Resultsmentioning
confidence: 97%
“…The increase in Δ E illustrates an increased content of Mn 3+ . The Mn valence can be calculated using the follow equation: v Mn = 9.67 1.27 × normalΔ E 3 s / eV …”
Section: Resultsmentioning
confidence: 99%
“…As the technology for modulating metal dispersion became more sophisticated, single‐atom catalysts had been developed in the field of electrocatalysis [31] . The single‐atom Pd catalyst facilitated the Volmer reaction and produced more H* favorable for dechlorination [32] In single‐atom catalysts, the metal catalysts were not aggregated because the individual metals were anchored by heteroatoms [33] . The metal single‐atom catalysts prepared in this way were able to achieve 100 % utilization [34] .…”
Section: Modulation Of Pd To Improve Ech Efficiencymentioning
confidence: 99%
“…31 Yan et al reported that a multifunctional surface construction involving a coating layer, spinel-layered heterostructure, and rich-in oxygen vacancies was successfully conducted through facile thermal reduction of the LMO particles with potassium borohydride as the reducing agent. 32 The surface/interface 33 of LMOs has been achieved by the reconstruction of a surface structure, for example, Wu et al put forward a feasible interfacial modification strategy in virtue of Mn 3 O 4 surface coating to construct a protective shell at the surface of LMOs. 34 The modified material exhibits a high ICE of 84.3% and the capacity retention is 95.6% at 1C after 200 cycles.…”
Section: Introductionmentioning
confidence: 99%